Historic Tales: The Romance of Reality. Vol. 13 (of 15), King Arthur (1) - Morris, Charles, 1833-1922; Malory, Thomas, Sir, -1471 (Salt Lake City, UT : Project Gutenberg, 2010)
"Historic Tales: The Romance of Reality. Vol. 13 (of 15), King Arthur (1)" by Charles Morris is a historical account written in the late 19th century. The book explores the legendary figure of King Arthur, focusing on themes of chivalry, valor, and the mythic origins of his reign. It delves into Arthur's early triumphs and the iconic magical sword, Excalibur, as well as the complexities of his relationships and battles as he establishes himself as king. The opening of the work sets the stage with a retelling of how King Arthur came to power, beginning with the death of his father, Uther Pendragon. In a time of chaos and anarchy, Merlin, the wizard, devises a test involving a miracle sword embedded in a stone, proclaiming that whoever can draw it will be the rightful king. Many noble lords attempt and fail until the young Arthur, still unaware of his royal heritage, succeeds in pulling the sword from the stone. This moment launches him into a tumultuous journey of battles and revelations about his lineage, ultimately leading to his coronation as king with the promise of great exploits ahead. (This is an automatically generated summary.)
How Arthur won the throne -- The deeds of Balin -- The treason of Morgan le Fay -- Lancelot du Lake -- The adventures of Beaumains -- Tristram of Lyonesse and the fair Isolde -- How Tristram came to Camelot.
Release date is 2010-04-06
E-text prepared by Christine Aldridge and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Arthurian romances; Malory, Thomas, Sir, active 15th century. Morte d'Arthur -- Adaptations